Welfare Beneficiary Community BUMDes Karya Dermawan Dusun Dalam Village - Muhammad Fauzi; Asa'ari Asa'ari; Arzam Arzam; Mursal Mursal; Zufriani Zufriani; Aidil Novia; Dafiar Syarif (Universitas Pendidikan Ganesha, 2021)
Dusun Dalam Village Government established a Village-Owned Enterprise (BUMDes) Karya Dermawan is a policy utilization. The main pillar was established BUMDes Karya Dermawan in accordance with the mandate of the objectives whose activities were oriented to encourage the welfare of the village community. Therefore, this study was conducted aimed at looking at the welfare provided by BUMDes Karya Dermawan Dusun Dalam village especially to the beneficiary community and compare the level of welfare before and after BUMDes Karya Dermawan was established. This study uses a descriptive quantitative approach, and data sourced from primary data by using Paired Sample t-Test as a data analysis tool. This study shows that BUMDes Karya Dermawan provides welfare to the beneficiary communities through businesses that have been established including Cooperatives; Alsintan; and Workshop, which is directly able to change or succeed in providing an increase in welfare for the beneficiary community after the establishment of BUMDes as evidenced by the results of the Paried Sample t-Test analysis. With this evidence of success, for all elements should give intensive attention; so that the development of BUMDes Karya Dermawan exists even more as a driver of community welfare. And also, integratedly invites and becomes a valuable lesson for existing villages to establish BUMDes or villages that already have BUMDes, but have not succeeded in providing a common thread for the welfare of their citizens.